The Gender Difference in the Association Between Early Onset of Drinking and Problem Drinking Between the U.S. and Japan. Issue 12 (2nd December 2018) - Tedor, Miyuki Fukushima; Quinn, Linda M.; Wilsnack, Sharon C.; Wilsnack, Richard W.; Greenfield, Thomas K.
ABSTRACT: Using comparable survey data from the GENACIS Project, collected from representative samples of people aged 20 to 70 years old in the U.S. ( n = 2, 598) and Japan ( n = 1, 734), this study examined, across these two diverse societies, the gender difference in the association between the early onset of drinking and the development of drinking problems. The results of this study suggest that there does not appear to be a cross-national causal relationship between the early onset of drinking and problem drinking because of significant country and gender variations in this association and because there is no association found among Japanese females. As hypothesized, the early onset of drinking predicted problem drinking among males more strongly than among females in both countries.